ANALISIS KUALITAS PELAYANAN PUBLIK DI RUMAH SAKIT INCE ABDUL MOEIS SAMARINDA - Alimul Hakim (Jurnal Paradigma (JP), 2017)
The Purpose of this study is to analyze and describe quality of public services and analyzes the factors that become supporting and quality public services General Hospital of Ince Abdul Moeis Samarinda. This research includes qualitative descriptive research. Descriptive research is to gain a clearer picture of the phenomena that occur in relation to the problems examined. The qualitative data is done by organizing data, translate it into the units, synthesize, organize into a pattern, choose which is important and which will be studied, and make conclusions from the results of the exposure can be told to others. Research instrument is a researcher himself, and once served as a means of collecting data. Researcher as research instrument aims to obtain valid data and reliable.